Oxytocin/Osteocalcin/IL-6 and NGF/BDNF mRNA Levels in Response to Cold Stress Challenge in Mice: Possible Oxytonic Brain-Bone-Muscle-Interaction - Camerino, Claudia; Conte, Elena; Carratù, Maria Rosaria; Fonzino, Adriano; Lograno, Marcello Diego; Tricarico, Domenico (Frontiers in Physiology, 2019)
Oxytocin (Oxt), Osteocalcin (Ost) and NGF/BDNF exert a protective function on bone, reproduction and cognition. Oxt/Ost are required for muscle regeneration. We investigated the gene response of muscle and the inter-organ communication following cold stress (CS). The mRNA levels of Ngf, Ost, Oxt, Bdnf and their receptors (p75ntr, Ntrk1, Gprc6a, Oxtr, Ntrk2), UCP1 and Il-6 in bone, brain, Soleus (SOL) and Tibialis anterioris (TA) muscles from 3 months-old mice exposed to CS were investigated. The expression of Myosin heavy-chain Mhc2b (fast-glycolytic), Mhc1 (slow-oxidative), Mhc2x and Mhc2a (fast-glycolytic-oxidative) were investigated. Mice were maintained at T=23°C (controls) or exposed to CS at 4°C for 6h and 5-days (5d). CS mice did not show signs of muscle degeneration. Ucp1 and Ngf genes were upregulated by 2 and 1.5 folds respectively in TA after 6h CS and Ntrk1 by 4 and 22 folds in SOL muscle after 6h and 5d CS, respectively; while p75Ntr was downregulated in both muscles after 6h CS. Bdnf was unaffected, while Ntrk2 was upregulated after 5d CS in TA. Ost was downregulated in SOL by 0.9-folds at 5d. Oxtr and Il-6 genes were upregulated respectively by 1 and 1.5 folds after 5d CS in SOL. Mhc2b was downregulated respectively by 0.96 and 0.88-folds after 6h and 5d CS in SOL. Mhc2a was downregulated by 0.88-fold after 5d CS in TA. Mhc1 and Mhc2x were not affected after CS. Regression analysis showed that changes in the expression levels of genes in TA and SOL muscles, bone and brain exposed to CS were regulated by IL6 and OXT. CS induced the potentiation of the slow-twitch phenotype of SOL which is in line with the metabolic need of the oxidative muscle following CS, and the potentiation of the slow-twitch phenotype in TA. OXT and IL6 coordinate a phenotype-dependent tonic effect of slow-twitch muscle; OXT regulates the inter-organ communication between brain and SOL muscle. Muscle tropism is maintained by NGF signaling following CS.